(untitled) (Zaporizhzhia Historical Review, 2021)
This article is devoted to the issues of investigating of the History of South Ukraine of the last quarter of XVIII century and especially of the so called New Dnieper Line of fortresses, building of which started in 1770. The most important element of this Line, as well as of the whole history of South Ukraine was Petrovska fortress. At the same moment the history of the South a New Dnieper Line is not deeply researched. This material is an attempt to enlarge other knowledge about New Dnieper Line and its important element ñ Petrovska fortress.